2016
DOI: 10.3390/cells5040042
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Application of Sirtuins and mTOR Signaling in the Control of Ovarian Functions

Abstract: The present short review demonstrates the involvement of sirtuins (SIRTs) in the control of ovarian functions at various regulatory levels. External and endocrine factors can affect female reproduction via SIRTs-mammalian target of rapamycin (mTOR) system, which, via hormones and growth factors, can in turn regulate basic ovarian functions (proliferation, apoptosis, secretory activity of ovarian cells, their response to upstream hormonal regulators, ovarian folliculo- and oogenesis, and fecundity). SIRTs and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
(105 reference statements)
0
28
0
1
Order By: Relevance
“…The ability of progesterone to inhibit ovarian follicular growth was associated with the reduction of granulosa cell proliferation, and the ability of testosterone to promote ovarian atresia associated with apoptosis (Sirotkin, 2014) suggested that the constituents of green tea can affect ovarian cell proliferation and apoptosis via changes in steroidal hormone output. Furthermore, the action of green tea molecules on ovarian cell steroidogenesis and other functions could result from their ability to affect ovarian cell luteinisation (Sirotkin, 2014), steroid hormone receptors (Sirotkin and Harrath, 2014), the sirtuin/ mTOR signalling pathway (Sirotkin, 2016), or to their antioxidant properties (Basini et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of progesterone to inhibit ovarian follicular growth was associated with the reduction of granulosa cell proliferation, and the ability of testosterone to promote ovarian atresia associated with apoptosis (Sirotkin, 2014) suggested that the constituents of green tea can affect ovarian cell proliferation and apoptosis via changes in steroidal hormone output. Furthermore, the action of green tea molecules on ovarian cell steroidogenesis and other functions could result from their ability to affect ovarian cell luteinisation (Sirotkin, 2014), steroid hormone receptors (Sirotkin and Harrath, 2014), the sirtuin/ mTOR signalling pathway (Sirotkin, 2016), or to their antioxidant properties (Basini et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To date, seven members of the sirtuin family have been identified in mammals (SIRT1-7), each member playing a role in ovarian function (for an extensive review, see [ 39 , 40 ]). In fact, damage impairing SIRT’s activity leads to fertility deficits [ 39 , 41 , 42 ].…”
Section: Resveratrol Effects On Femalesmentioning
confidence: 99%
“…In swine granulosa cells, resveratrol increased SIRT1 mRNA and protein level in a dose-dependent fashion, accelerating cell apoptotic rate and follicular atresia [ 47 ]. Resveratrol supplemented in cultured porcine ovarian granulosa cells determined SIRT1 protein increase and apoptosis, promoting testosterone and estrogen release, while inhibiting cell proliferation [ 42 ].…”
Section: Resveratrol Effects On Femalesmentioning
confidence: 99%
“…Apoptosis and steroidogenesis are decreased in porcine granulosa cells. Rapamycin promotes apoptosis in healthy porcine ovarian cells and suppresses follicular growth and maturation in rodents (Sirotkin, ). Most available observations suggest that mTOR blockers can suppress basic functions, promote apoptosis, and prevent or reverse the influence of physiological FSH levels on these processes (Sirotkin, ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Rapamycin promotes apoptosis in healthy porcine ovarian cells and suppresses follicular growth and maturation in rodents (Sirotkin, ). Most available observations suggest that mTOR blockers can suppress basic functions, promote apoptosis, and prevent or reverse the influence of physiological FSH levels on these processes (Sirotkin, ). Growth factor receptor/PI3K signaling induces cell proliferation via the AKT and ERK1/2 pathway (Arumugam et al ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%